2012
DOI: 10.1097/ico.0b013e318247eaed
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Stripping Automated Endothelial Keratoplasty Performed by Cornea Fellows

Abstract: Outcomes of DSAEK performed by cornea fellows supervised by the faculty members seems to be fairly acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Our experience of DSEK in CHED is limited to this case. The degree of stromal thickening and scarring and the presence of nystagmus, which can lead to detachment of the endothelial graft, contribute to poor DSEK outcomes in CHED 20. Mittal et al noted that DSEK is technically challenging in CHED because of the poor view through the opaque cornea and difficulty in Descemet’s membrane removal, which is firmly attached 3.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience of DSEK in CHED is limited to this case. The degree of stromal thickening and scarring and the presence of nystagmus, which can lead to detachment of the endothelial graft, contribute to poor DSEK outcomes in CHED 20. Mittal et al noted that DSEK is technically challenging in CHED because of the poor view through the opaque cornea and difficulty in Descemet’s membrane removal, which is firmly attached 3.…”
Section: Discussionmentioning
confidence: 99%
“…[3536373839404142434445464748495051525354555657585960616263646566676869707172] Figs. 1 and 2 show the postoperative outcomes after DSAEK and ultrathin DSAEK, respectively.…”
Section: Outcomes Of Descemet Stripping Automated Endothelial Keratopmentioning
confidence: 99%
“…Analysis of the available studies suggests endothelial cell loss in the range of 25%–61% at 3-year follow-up. [1035447273] At 5 years follow-up, it has been reported to be around 51.9%. [52]…”
Section: Outcomes Of Descemet Stripping Automated Endothelial Keratopmentioning
confidence: 99%
“…The authors reported a primary graft failure rate of 21.8% for the level 1 surgeon compared with 1.5% for the level 5 surgeon. 6 Hashemi et al reviewed the results of DSAEK surgery for cornea fellows and found graft detachment in 17 eyes (21.7%) and graft failure in 8 eyes (10.2%), 5 compared with a graft detachment rate of 2.7 and 8.9% and a graft failure rate of 4.1 and 3.0% in attending surgeons at a tertiary academic center in eyes without previous glaucoma surgery. 11,12 Given this steep learning curve, cornea specialists are hesitant to allow residents to be primary surgeons for DSAEK surgery, and to the best of our knowledge, we could not find any other publications in the literature discussing the results of residents as primary surgeons for DSAEK (PubMed search on May 14, 2017, using the terms "DSAEK" and "resident," or "DSAEK" and "novice").…”
Section: Discussionmentioning
confidence: 99%
“…Our graft detachment rate of 0% and primary graft failure rate of 11% are far better than those discussed in the literature for novice surgeons. 5,6 There are several technique variations that, we think, make our procedure easier for novice surgeons:…”
Section: Discussionmentioning
confidence: 99%